2009
DOI: 10.4049/jimmunol.0901383
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Require STAT-1 Phosphorylated at Its Transactivating Domain for the Induction of Peptide-Specific CTL

Abstract: Phosphorylation of transcription factor STAT-1 on Y701 regulates subcellular localization whereas phosphorylation of the transactivating domain at S727 enhances transcriptional activity. In this study, we investigate the impact of STAT-1 and the importance of transactivating domain phosphorylation on the induction of peptide-specific CTL in presence of the TLR9-dependent immune adjuvant IC31. STAT-1 deficiency completely abolished CTL induction upon immunization, which was strongly reduced in animals carrying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 56 publications
(46 reference statements)
4
29
0
Order By: Relevance
“…These findings are consistent with recent observations that type I IFNs can act directly on CD8 + T cells, facilitating clonal expansion and differentiation into effector and memory CD8 + T cells (16,31,41). Furthermore, other studies have shown that immunizations with synthetic CD8 + T cell peptide epitopes or with protein Ags (requiring cross-presentation) are strongly enhanced in the presence of type I IFN-inducing TLR ligands (42)(43)(44).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings are consistent with recent observations that type I IFNs can act directly on CD8 + T cells, facilitating clonal expansion and differentiation into effector and memory CD8 + T cells (16,31,41). Furthermore, other studies have shown that immunizations with synthetic CD8 + T cell peptide epitopes or with protein Ags (requiring cross-presentation) are strongly enhanced in the presence of type I IFN-inducing TLR ligands (42)(43)(44).…”
Section: Discussionsupporting
confidence: 81%
“…However, according to recent studies (16,31), it is more likely that signals downstream of the IFNAR contribute to increased survival and effector functions of CD8 + T cells. At this point, we cannot exclude a potential synergistic effect between direct type I IFN signaling on CD8 + T cells and additional signals provided by other cell types, as it has been reported that the immunostimulatory activity of type I IFN stems, at least in part, from its ability to induce DC maturation (44,49).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanistic basis for this immunodeficiency involves impaired memory development, CTL generation, and DC function (63)(64)(65). Our results now provide evidence that Stat1 is an inhibitor of Tregs and that in the absence of Stat1, enhanced expansion of Tregs may lead to blunting of the Th1 response, thereby contributing to immunosuppression.…”
Section: Discussionmentioning
confidence: 49%
“…The latter has been shown to be important for maximal transcriptional activity of Stat1/3/4 but not of Stat5a and Stat5b. 22 Biochemical and biologic functions of Stat serine phosphorylation also include DNA binding, 23,37 cofactor association, 38 immune responses, 39,40 and transformation. 41,42 Interestingly, we found the C-terminally mapped serines of Stat5a (Ser725/779) to be highly phosphorylated in human bcr/abl ϩ CML samples, human lymphoma cell lines, primary leukemia patient samples, and Ba/F3 cells overexpressing different fusion tyrosine kinases.…”
Section: Discussionmentioning
confidence: 99%